Environmental Stability of MXenes as Energy Storage Materials - Li, Xinliang; Huang, Zhaodong; Zhi, Chunyi (Frontiers in Materials, 2019)
In the past decade, MXenes family have undergone considerable development and have been widely investigated in various research fields, relying on their excellent physicochemical properties. Benefiting from the increasingly versatile preparation methods and the continued discovery of new members, their large-scale application has already been underway, with energy storage fields including supercapacitors and batteries leading. The synthesis methods and processing environment of MXenes, which are closely strictly to the microstructure, surface chemistry, and electronic properties, have attracted great attention. In this review, we review the phylogeny of MXenes materials in recent years, mainly focusing on the synthesis process and environmental stability.